ALTERNATIVA PARA A FIXAÇÃO DE SUBSTITUTOS DO LIGAMENTO CRUZADO EM CÃES - Basso, Paula C.; Serafini, Gabriele M. C.; Fritzen, Henrique S.; Schossler, João E.; Libardoni, Renato d. N. (Salão do Conhecimento, 2013)
Resumo